Does an ethic matter to predict misreporting behavior? - Ascaryan Rafinda; Triani Arofah; Rasyid Mei Mustafa; Halomoan Ompusunggu (Journal of Economics, Business, and Accountancy Ventura, 2015)
This study was conducted to verify the assertions of various previous studies examining the relationship between individual moral reasoning and ethical behavior. Those studies conclude that individuals with good moral reasoning tend to behave better. However, they do not consider situational factors that can change this individual behavior. This study attempts to consider situational factors linked to the individual as antecedents of unethical behavior. Situational factors are taken into account for verifying whether an individual with high moral reasoning in a situation that supports unethical actions will be acting unethically. The data were taken by experimental methods 2 × 1 between the subjects where the manipulation is by positive and negative treatment given to see the effect against their intentions to do fraud. The level of moral reasoning is measured using a test instrument which defines the issue for categorizing the participants with high morale and low morale. Difference- t-test was performed to investigate the differences between the two groups experimental. It shows that situational factors are things that can affect a person's ethical or unethical act regardless of their moral reasoning abilities. The implication is that to minimize the unethical behavior of employees, the company can focus on situational factors rather than individual moral.